2009
DOI: 10.1136/jnis.2009.000331
|View full text |Cite
|
Sign up to set email alerts
|

Long term clinical and angiographic outcomes with the Wingspan stent for treatment of symptomatic 50–99% intracranial atherosclerosis: single center experience in 51 cases

Abstract: The use of the Wingspan stent in patients with ≥50% symptomatic intracranial stenosis is associated with good long term clinical outcome. One stroke occurred after the first 30 days, suggesting a significant stabilization of the adverse event rate after the first month.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
(32 reference statements)
1
15
0
Order By: Relevance
“…The technical success rate for stent implantation was 97% in our study, which was in accordance with previously reported success rates [an unsuccessful stent implantation occurred in our patient who had residual stenosis (60%) in the MCA]. The ischemic stroke and mortality rates after the procedure have ranged from 3.2 to 10% [26,27,28]. Suh et al [29] reported on cases with intracranial stenosis that were ≥70% and were treated with various types of BMS.…”
Section: Discussionsupporting
confidence: 91%
“…The technical success rate for stent implantation was 97% in our study, which was in accordance with previously reported success rates [an unsuccessful stent implantation occurred in our patient who had residual stenosis (60%) in the MCA]. The ischemic stroke and mortality rates after the procedure have ranged from 3.2 to 10% [26,27,28]. Suh et al [29] reported on cases with intracranial stenosis that were ≥70% and were treated with various types of BMS.…”
Section: Discussionsupporting
confidence: 91%
“…In that study, the mean imaging follow-up time was 8.5 months rather than 12 months (range 3–15.5) 8. In a single-center study in the USA the ISR rate was 24% (7/29) on DSA at a mean of 8.6 months (range 3–20) 10. In another paper based on the same American multicenter study, the ISR was noted to be associated with younger age (45.2% (14/31) at ≤55 years of age vs 23.2% (15/62) at >55 years) and with location of the lesion in the internal carotid artery (43.7% (14/32) vs 24.6% (15/61) at other locations) 9.…”
Section: Discussionmentioning
confidence: 88%
“…According to previous reports, ISR was observed in 24%-35% of the patients, 9,10,19,20) but the mean follow-up period was 8 months in many of these reports and 2-3 months in some. 19,20) In our study, on serial evaluations until 1 year after the procedure, the percent stenosis increased at 3-6 months compared with the state immediately after the procedure in seven lesions (7/11, 64%) but decreased at 1 year (3M vs. 1Y: p = 0.080, 6M vs. 1Y: p = 0.085), and the luminal diameter was increased at 1 year compared with the state immediately after the procedure in six lesions (6/12, 50%).…”
Section: Discussionmentioning
confidence: 99%
“…19,20) In our study, on serial evaluations until 1 year after the procedure, the percent stenosis increased at 3-6 months compared with the state immediately after the procedure in seven lesions (7/11, 64%) but decreased at 1 year (3M vs. 1Y: p = 0.080, 6M vs. 1Y: p = 0.085), and the luminal diameter was increased at 1 year compared with the state immediately after the procedure in six lesions (6/12, 50%). As a result, ISR was observed in two lesions at 3-6 months but only one lesion (8.3%) at 1 year.…”
Section: Discussionmentioning
confidence: 99%